AKULTURASI NILAI-NILAI PENDIDIKAN ISLAM DALAM ADAT PERKAWINAN BUGIS WAJO - Tahir, Andi; A, Sulaeman; F, Fatimah; Aspila, Ayu (JURNAL AL-QAYYIMAH, 2022)
One of the interesting things to study is the acculturation of Islamic educational values in the Bugis Wajo marriage custom. culture and customs are ancestral heritage that must be preserved to this day even though times are modern but culture and customs should not be shifted because there are Islamic educational values in them. The research method used in this journal is qualitative research using a phenomenological approach, namely a phenomenological approach. a form of approach that seeks to reveal facts, symptoms and events objectively. All data obtained were analyzed descriptively with several approaches, namely historical, sociological, historical and cultural as well as education. The results of the study show that marriage customs are the result of all human thoughts that unite into people's behaviors which are usually inherited from generation to generation from ancestors. The Bugis community is a nervous society with customary principles and values and Islamic religious teachings that have Islamic educational values. A proposal is an initial process carried out by a man, and sends his family to the house of a woman who wants to propose to discuss the continuity of marriage. . Mappaccing is self-cleaning from everything, Allah SWT likes clean people as contained in the hadith which says that part of cleanliness is faith. Ijab Kabul is a sacred thing every time you get married and without a Kabul consent, marriage is not valid. Sungkeman is a child's honor to his parents and the bride and groom ask for the blessing of their parents so that their marriage lasts until their grandparents.